Are Academics Wrongly Assuming Bioscience Students Have the Transferable Skills and IT Competency They Need to Be Successful Beyond the Degree? - Bashir, Amreen; Bashir, Shahreen; Hilton, Anthony C. (Frontiers in Education, 2017)
Acquisition and development of key transferable skills is an important requirement for all graduate employees. The aim of the current study was to investigate a potential skills shortage in bioscience students and, if revealed, explore ways of addressing it. A research questionnaire, which included mixed methodology, was used to collate information from a cohort of students across levels four, five and six enrolled on Biological and Biomedical Science undergraduate programmes. A total of 131 students participated in the study. The questionnaire was designed to establish students’ confidence using packages such as the Microsoft Office Suite and whether they required additional support with certain programmes; further areas explored students’ self-assessment of key skills such as written communication, referencing, self-confidence, presentation skills and team working. No statistically significant gender differences (males n = 49; females n = 82) were observed in participant responses (p> .05). Of the total number of students included in the survey, 91% rated themselves as competent using Word and 64% felt least confident using statistical software and performing statistical analysis in Microsoft Excel. Comparing responses by year of study revealed no statistical differences in reported abilities (p> .05). These findings indicate areas of potential key skills shortages, particularly using data handling software, which may not be sufficiently addressed if prior knowledge is incorrectly assumed. Nearly half of students (50% of level six students) who were graduating felt unprepared performing statistical analysis in Excel. Inclusion of an IT component to support skills development in data handling software at Level 4 is recommended and teaching key software packages is necessary. Furthermore, opportunities for students to develop their presentation skills and report writing abilities are required. This in turn should improve the student experience and develop the transferable skills which are increasingly sought by employers.